Eleven‐year trends of inpatient pacemaker implantation in patients diagnosed with sick sinus syndrome. (22nd June 2017) - Guha, Avirup; Xiang, Xiao; Haddad, Devin; Buck, Benjamin; Gao, Xu; Dunleavy, Michael; Liu, Ellen; Patel, Dilesh; Fedorov, Vadim V.; Daoud, Emile G.
Abstract: Background: Pacemakers (PM) are used for managing sick sinus syndrome (SSS). This study evaluates predictors and trends of PM implantation for SSS. Methods: Patients were identified from the National Inpatient Sample dataset (2003–2013). Included patients were ≥18 years old, had a diagnosis of sinus node dysfunction and atrial arrhythmia (i.e., SSS). Patients who died, transferred out, who had prior device, or had a defibrillator or resynchronization therapy device implanted were excluded. Included patients were then stratified by if a PM was implanted. Data regarding SSS, trends of PM utilization, and multivariable models of factors associated with PM implantation are presented. Results: Note that 328, 670 patients satisfied study criteria. This study compared patients who underwent (87.4%) PM implantation to those who did not undergo (12.6%) PM implantation. The annual trends for hospitalization with SSS and PM placement have been decreasing (P <0.001). Variables associated with lower likelihood for PM implantation include young age, female sex, non‐Caucasian race, chronic heart failure, Charlson Comorbidity Score ≥1, emergency room and weekend admission, hospital stay ≤3 days, and high cardiology inpatient volume. Greater likelihood for PM implantation was associated with hyperlipidemia, hypertension, and hospitals that were either private, large, Northeastern location, or with high cardiac procedural volume. Conclusions: Analyzing 11‐year data from a national inpatient database demonstrate a number of relevant variables that impact PM utilization that include not only clinical but also nonclinical variables such as socioeconomic status, gender, and hospital features. Racial and gender bias toward PM implantation are unchanged and persist through 2013.